Evaluasi Kinerja Pemindahan Overburden Ditinjau Dari Produktivitas Alat Gali- Muat dan Alat Angkut di Front Kerja 2 TB 2.2 Tempilang Kabupaten Bangka Barat Mitra PT Timah (Persero) Tbk: (Performance Evaluation Of Overburden Removal Reviewed From Load Haulage Equipments and Conveyance Productivity in Work Front 2 of TB 2.2 Tempilang West Bangka Regency of PT Timah (Persero) Tbk’s Partner - Fatimah, Desi; Tono, E.P.S.B Taman; Irvani, Irvani (MINERAL, 2016)
TB 2.2 Tempilang is managed by partner of PT Timah (Persero) Tbk. Mining system that applied is asystem of mechanical mine, where mining activities carried out by moving the overburden materialprior to mine kaksa layer. The problem that occurs was the productivity of conveyance on the actualcondition only 98.76% of target had been determined, which led to their failure in overburden removalvolume amounted to 1.24%. Therefore, it was necessary to do an evaluation of the performanceaffecting factors of load haul equipment and conveyance in the field. Evaluation was carried out bycalculating the value of productivity, work efficiency and Match factor. The data required includedcycles time data, effective working time, the amount of bucket loading, the type of overburden materialand haul road geometry. Then the data was processed using the formula of mechanical soil removaland analyzed based on the literature related to the problem. The factors causing productivityconveyance has not reached the target after the evaluation due to low efficiency of work, the leastamount of bulk bucket loading, and the low value of match factors. The Alternatives can be done toimprove the productivity of conveyance is to increase the effective work time, additional of bucket loadhaul equipments and additional of conveyances. Effective work time should be increased from 12.34hours to 14.23 hours, so the work efficiency become 79.03% from 68.58% to the achievement ofproduction is 113.80%. Bulk bucket should be added from 15 times to 20 times, so the productivitybecome 131.68 m3/hour of 98.67 m3/hour. Conveyance which is originally 2 units coupled into 3 units,resulting in a change of match factor equipment performance from 0.69 to 1.04 with the achievementof production is 141.14%.